SEEDLINGS PRODUCTION OF ORNAMENTAL SPECIES IN DIFFERENT TIMES AND SUBSTRATES (Colloquium Agrariae. ISSN: 1809-8215, 2021)
This work aimed to evaluate the seedlings production of Petunia x hybrida and Gomphrena globosa at different times and substrates based on agricultural residues. A completely randomized experimental design was adopted, in a factorial scheme, with treatments consisting of four replications and the experimental unit formed by ten plants. The flower species Petunia x hybrida and Gomphrena globosa were cultivated in five substrate compositions and in two seasons, with sowing carried out in April and June for Petunia x hybrida and April and October for Gomphrena globosa. The substrates were composed using commercial substrate (SC), bovine manure (EB), earthworm humus (HM) and rice husk ash (CC), in volumetric proportions: (S1) 100% SC; (S2) 40% SC + 20% EB + 20% HM + 20% CC; (S3) 60% SC + 20% HM + 20% CC; (S4) 60% SC + 20% EB + 20% CC; and (S5) 80% SC + 20% EB. Emergence, emergence speed index, height, number of leaves, length of the largest leaf, length of the largest root, dry mass of the aerial part, dry mass of the root system and total dry mass were evaluated. The seedlings growth of the Petunia x hybrida and Gomphrena globosa changed according to the characteristics of the substrates and the growing seasons. The substrate composed with 80% commercial substrate and 20% bovine manure showed similar or superior results to the commercial substrate and can be used in order to reduce production costs without prejudice to the seedlings growth. The cultivation of Petunia x hybrida in April resulted in seedlings with greater height, leaf length and greater accumulation of phytomass. The Gomphrena globosa seedlings showed greater development of the aerial part and the root system, in addition to greater accumulation of phytomass when cultivated in October.